2015
DOI: 10.4103/0971-5916.166595
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to anti-retroviral therapy & factors associated with it: A community based cross-sectional study from West Bengal, India

Abstract: Background & objectives:Failure to adhere to anti-retroviral therapy (ART) can lead to a range of unfavourable consequences impacting upon people living with HIV (PLH) and society. It is, therefore, paramount that ART adherence is measured in a reliable manner and factors associated with adherence are identified. Lack of such data from West Bengal necessitated undertaking the current study.Methods:Participants were included during August-October, 2011 from three Drop-In-Centres (DICs) from the three districts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…[ 15 18 23 ] Apart from the distance, none of socioeconomic factors were found to be significantly associated – which is in concordance with the various studies done in India, as most of these studies were done in similar centers getting free ART from NACO. [ 8 15 23 24 ] Among the therapy-related dimension, we found nonadherence to be significantly associated with (a) Drug-related side effect and (b) Efavirenz-combined therapy. This supports the findings of previous studies.…”
Section: Discussionmentioning
confidence: 92%
“…[ 15 18 23 ] Apart from the distance, none of socioeconomic factors were found to be significantly associated – which is in concordance with the various studies done in India, as most of these studies were done in similar centers getting free ART from NACO. [ 8 15 23 24 ] Among the therapy-related dimension, we found nonadherence to be significantly associated with (a) Drug-related side effect and (b) Efavirenz-combined therapy. This supports the findings of previous studies.…”
Section: Discussionmentioning
confidence: 92%
“…Other studies have also reported different predictors of adherence to treatment in different populations and settings. Disclosure of HIV status [36, 37], education [36], duration on ART treatment [37] and alcohol use [36] have all been reported as predictors of adherence to treatment. These were not however elicited in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Patients in that study revealed numerous reasons for their actions, ranging from repoting being very busy to take their treatment to forgetfulness, drinking alcohol and substance use [ 12 ]. Moreover, a study in India reported that only 73% of patients on ART took their treatment with at least or over 95% adherence [ 13 ]. Furthermore, patients’ perceived erectile dysfunction may be regarded as a relevant problem for HIV-infected persons on anti-retroviral therapy [ 14 ] and has been strongly associated with suboptimal ART adherence [ 15 ].…”
Section: Introductionmentioning
confidence: 99%